2015
DOI: 10.1186/s12913-015-0751-1
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a care pathway for elderly patients, a comparative qualitative process evaluation in primary care

Abstract: BackgroundIn Central Norway a generic care pathway was developed in collaboration between general hospitals and primary care with the intention of implementing it into everyday practice. The care pathway targeted elderly patients who were in need of home care services after discharge from hospital. The aim of the present study was to investigate the implementation process of the care pathway by comparing the experiences of health care professionals and managers in home care services between the participating m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
110
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(122 citation statements)
references
References 31 publications
4
110
0
8
Order By: Relevance
“…One reason can be that implementation of complex interventions, requiring behavioural changes for the health personnel involved, takes time and require targeted efforts before the intervention is settled in the organisation [32]. This became evident in our previous implementation study [13] where we found that enthusiasm and positive attitude to the intervention was not sufficient for a successful implementation. Considerable efforts were needed to make the home care professionals understand their responsibilities in PaTH and how to assess the patients by using the checklists.…”
Section: Discussionmentioning
confidence: 99%
“…One reason can be that implementation of complex interventions, requiring behavioural changes for the health personnel involved, takes time and require targeted efforts before the intervention is settled in the organisation [32]. This became evident in our previous implementation study [13] where we found that enthusiasm and positive attitude to the intervention was not sufficient for a successful implementation. Considerable efforts were needed to make the home care professionals understand their responsibilities in PaTH and how to assess the patients by using the checklists.…”
Section: Discussionmentioning
confidence: 99%
“…Experiences with such a pathway have not previously been described. Furthermore, very few studies of integrated care interventions across the hospital – primary care continuum performed a detailed process evaluation [24]. A study by Rosstad and colleagues showed that the pathways improved collaboration between professionals but that implementation was demanding and required a lot of work [24].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, very few studies of integrated care interventions across the hospital – primary care continuum performed a detailed process evaluation [24]. A study by Rosstad and colleagues showed that the pathways improved collaboration between professionals but that implementation was demanding and required a lot of work [24]. A study focusing on providers’ perceptions of delivering integrated care found that professionals’ bottom-up involvement during implementation is key to success [25].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, facilitating seamless patient pathways is crucial to improving experiences of continuity of care and delivering coordinated high‐quality care for the increasing group of frail older patients residing in the community (Endelin et al, ; Neiterman, Wodchis, & Bourgeault, ; Pellett, ). Research has shown that one means to facilitate holistic pathways and continuity of care for older patients is to implement person‐focused checklists (Røsstad et al, ; Røsstad, Garåsen, Steinsbekk, Sletvold, & Grimsmo, ).…”
Section: Introductionmentioning
confidence: 99%